Espectrometria de massas e análise discriminante na avaliação de especiarias orgânicas e convencionais - Galvao, Monica Adriely (2024)
Conventionally grown foods frequently contain chemical residues, such as fertilizers and pesticides, which may pose potential health risks. In contrast, organic foods are cultivated without synthetic inputs, adhering to rigorous certification standards. Spices, highly valued since the 14th and 15th centuries in Western Europe for their potent flavors and aromas, are experiencing increased demand due to a growing consumer preference for natural products. However, the limited availability of conclusive scientific data on the advantages of organic foods, alongside their higher costs, presents ongoing challenges to their production and market acceptance. This study presents a rapid and innovative analytical approach for differentiating between organic and conventional spices. Employing matrix-assisted laser desorption/ionization time-offlight mass spectrometry (MALDI-TOF) and independent component analysis with discriminant analysis (IC-DA), this method enables precise evaluation of spices, such as cinnamon, oregano, rosemary, and mint, independent of cultivation practices. This approach promises to be an effective tool for authenticating organic and conventional foods, enhancing food safety measures and bolstering consumer confidence.